2009
DOI: 10.5713/ajas.2009.80326
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Production Performance of Angora Rabbits under Sub-temperate Himalayan Conditions

Abstract: An experiment of one-year duration was conducted on sixteen adult male German Angora rabbits under sub-temperate Himalayan conditions, to assess the effect of seasons on their body weight, wool production and quality, plane of nutrition and the digestibilities of nutrients. The daily meteorological attribute viz. minimum and maximum temperature; relative humidity and rainfall were recorded during winter (October to March), summer (April to June) and rainy (July to September) seasons. Biological parameters viz.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
0
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
3
0
0
Order By: Relevance
“…This finding is in accordance with the findings of Sood et al, (2007), Rafat et al, (2007 and, Bhatt and Sharma (2009) in Angora rabbits. However, Sambher et al, (1999) reported non-significant effect of season of birth on the trait in German Angora rabbits.…”
Section: Effect Of Year Of Birth Season Of Birth and Sex On Annual Wool Yieldsupporting
confidence: 94%
See 1 more Smart Citation
“…This finding is in accordance with the findings of Sood et al, (2007), Rafat et al, (2007 and, Bhatt and Sharma (2009) in Angora rabbits. However, Sambher et al, (1999) reported non-significant effect of season of birth on the trait in German Angora rabbits.…”
Section: Effect Of Year Of Birth Season Of Birth and Sex On Annual Wool Yieldsupporting
confidence: 94%
“…The differences in wool production due to season of birth may be attributed to changes in feed quality, its intake and other changes in managemental practices. Similar significant seasonal effects on wool yield at different clips have also been reported by Sood et al, (2007) and, Bhatt and Sharma (2009) in German Angora rabbits. The wool yield differed significantly among different seasons with the highest and the lowest during winter and summer, respectively.…”
Section: Effect Of Year Of Birth Season Of Birth and Sex On Wool Yield At Different Clipssupporting
confidence: 87%
“…The wool yield at I, II and III clip differed significantly among different seasons with the highest yield during winter season followed by autumn season. Similar significant seasonal effects on wool yield at different clips were reported by Sood et al (2007), Bhatt and Sharma (2009) and Sarma et al (2020) in German Angora rabbits. The growth before weaning would be more dependent on maternal effects and thus effect of season could be more important after weaning.…”
Section: Effect Of Season Of Kindlingsupporting
confidence: 87%
“…Animals after weaning at 42 d of age were kept individually in all wire cages of standard dimensions under similar housing and management conditions. Rabbits were fed concentrate, containing 15 to 20% crude protein, in graded quantity from 30 to 140 g at different ages and seasonal grasses ad libitum (Bhatt and Sharma, 2009). Records of weaning weights were obtained at 42 d of age; whereas of clip I was obtained at 52 d of age and subsequent clips (II and III) after regular intervals of 75 days.…”
Section: Methodsmentioning
confidence: 99%